Sodium Valproate Inhibits the Growth of Human Cholangiocarcinoma In Vitro and In Vivo - Wang, Bing (Hindawi Publishing Corporation, 2013)

(untitled)
Background. None of treatment options for Cholangiocarcinoma (CCA), including surgery, adjuvant radiotherapy and chemotherapy, and ultimately liver transplantation, have been shown to substantially improve the survival rate in patients with CCA. Valproic acid (VPA), a histone deacetylase inhibitor, has been shown to display potent antitumor effects. In this study, sodium valproate, the clinically available form of VPA, was tested for its ability to inhibit the growth of cholangiocarcinoma cells, both in vitro and in vivo. Materials and Methods. Cholangiocarcinoma cells (TFK-1, QBC939, and CCLP1) of different origins were treated with sodium valproate to determine their effects on cell proliferation and differentiation, cell cycle regulation, apoptosis, and autophagy. The in vivo effects of sodium valproate on cholangiocarcinoma growth were assessed using a xenograft mouse model injected with TFK-1 cells. Results. Sodium valproate inhibited cholangiocarcinoma cell growth by inducing cell cycle arrest, cell differentiation, and apoptosis; sodium valproate effects were independent of autophagy. Tumor growth inhibition was also observed in vivo using TFK-1 xenografts. Conclusion. The in vitro and in vivo outcomes provide preclinical rationale for clinical evaluation of sodium valproate, alone or in combination with other drugs, to improve patient outcome in cholangiocarcinoma.